Contextual-Based Student Work Sheet Development in Mathematics Class IV at SD Negeri 206 Simpang Nibung - Wulandari, Wulandari; Rosalina, Elya; Kusnanto, Raden Angga Bagus (Universitas Trunojoyo Madura, 2023)
This study aims to develop teaching material products in the form of Contextual-Based Student Worksheets in Mathematics Class IV SD Negeri 206 Simpang Nibung which are valid and practical to use in the learning process. The research method is RD (Research and Development), using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques used are observation, interviews and questionnaires. Data analysis techniques using a scalelikert and scalegutman. The results of the research based on the analysis of the linguist's assessment showed 0.80 and the validation results of media experts were 0.78 and the results of material validation were 0.85. Overall the results of the analysis and calculation of the value of the questionnaire from the team of experts, contextually based Student Worksheets fall into the high category with a percentage of 0.81. While the results of the teacher practicality test are classified as very practical and the results of the trialsone to one classified as very practical as well as the results of trialssmall group very practical. The overall results of the practicality test are in the very practical category with a percentage of 87.6% so that it can be concluded that contextually based Student Worksheets in Mathematics are valid and practical to use.